CF3SO3H-enabled cascade ring-opening/dearomatization of indole derivatives to polycyclic heterocycles. Issue 20 (29th April 2021) - Yao, Zhengdong; Feng, Huangdi; Xi, Hui; Xi, Chuanjun; Liu, Weiping
Abstract : A novel dearomatization process to produce fused polycyclic indolines via a CF3 SO3 H-mediated cascade ring-opening of a β-lactam and hydroaminative cyclization is demonstrated. Abstract : A novel dearomatization process to produce fused polycyclic indolines via a CF3 SO3 H-mediated cascade ring-opening of a β-lactam and hydroaminative cyclization is demonstrated. It provides a new strategy for the synthesis of important polycyclic indoline-2-amine derivatives in moderate to excellent yields, as well as with good functional group tolerance. Moreover, transformation of the product was performed to deliver the corresponding acid, alcohol and amide smoothly.